2002
DOI: 10.1128/jcm.40.4.1174-1180.2002
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant BBK32 Protein in Serodiagnosis of Early and Late Lyme Borreliosis

Abstract: Borrelial protein BBK32 was evaluated as an antigen in the serodiagnosis of early and disseminated Lyme borreliosis (LB). bbk32 was cloned and sequenced from eight isolates of the three pathogenic Borrelia species. The identities between the amino acid sequences of the BBK32 proteins from Borrelia burgdorferi sensu stricto, B. garinii, and B. afzelii isolates were 71 to 100%. By immunoglobulin G (IgG) Western blotting (WB) or enzyme-linked immunosorbent assay (ELISA), up to 74 and 100% of acute-and convalescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 38 publications
(38 reference statements)
1
33
1
Order By: Relevance
“…However, our recent Abbreviations: EM, erythema migrans; LB, Lyme borreliosis. study suggested species-specific variations in the immune responses to the variant BBK32 proteins in early LB (Heikkilä et al, 2002). The rBBK32 antigen originating from a local B. afzelii strain appeared to be superior to the other heterologous rBBK32 variants.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, our recent Abbreviations: EM, erythema migrans; LB, Lyme borreliosis. study suggested species-specific variations in the immune responses to the variant BBK32 proteins in early LB (Heikkilä et al, 2002). The rBBK32 antigen originating from a local B. afzelii strain appeared to be superior to the other heterologous rBBK32 variants.…”
Section: Introductionmentioning
confidence: 97%
“…Serum samples were collected from patients with clinically documented or culture-or PCR-confirmed EM from Finland, Germany, Slovenia and the USA. All 23 Finnish sera were from culture (n ¼ 18) and/or from PCR (n ¼ 21) proven patients taken at the time of diagnosis (acute) and 1-3 months after treatment (convalescent) (Heikkilä et al, 2002). In the 23 patients with EM, genotyping by PCR analysis (Junttila et al, 1999) showed B. afzelii in 17 and B. garinii in 4 of the skin biopsies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations